DEVELOPING AN INTENSIVE COURSE MODEL IN IMPROVING ENGLISH LANGUAGE SKILLS OF STUDENTS OF EARLY CHILDHOOD ISLAMIC EDUCATION DEPARTMENT (PIAUD) - Jumrah, Jumrah (International Journal of Language Education, 2019)
Mastery of foreign languages is one of the important demands at all levels of education today. This has been demonstrated by government regulations that make English subjects a compulsory subject for students to learn from elementary school to higher education, especially after the application of the KKNI curriculum, English courses have become national subjects for all study programs despite scientific disciplines taken is not related to English. The Early Childhood Islamic Education (PIAUD) study program at State Islamic University of Mataram also makes English Language Courses a compulsory subject that must be taken by students in the first semester. Based on the results of observations and pre-test results conducted by researchers, the English language skills of PIAUD study program students are very low. Almost all PIAUD students are still at the beginner level. Therefore, this study aims to: first, to produce an intensive course model that can improve English language skills of PIAUD Study Program students, second, to produce teaching materials used in intensive courses that can improve the English language skills of PIAUD Study Program Students. This study uses a descriptive approach with the aim of describing the object of research or the results of research. The data is collected through tests, questionnaires, and interviews. the results of the study were then analyzed by normalized gain measurements and getting the Pretest value for this trial was 66.3 while the post test results were 84.6 so that the gain obtained was 0.28. this value has met the requirements. and it can be concluded that the instructional materials made have a positive impact on improving students' English skills.